An updated overview of diamond-like carbon coating in tribology - Al Mahmud, K.A.H.; Kalam, M.A.; Masjuki, Haji Hassan; Mobarak, H.M.; Zulkifli, N.W.M. (2015)
During the last two decades, the industry (including scientists) has focused on diamond-like carbon (DLC) coating because of its wide range of application in various fields. This material has numerous applications in mechanical, electrical, tribological, biomedical, and optical fields. Severe friction and wear in some machine parts consumes high amount of energy, which makes the process energy inefficient. Thus, DLC coating can be an effective means to lower the friction and wear rate. Some important process variables that affect the tribological characteristics of DLC coating are adhesion promoter intermediate layer, substrate surface roughness, hydrogen incorporation or hydrogen non involvement, and coating deposition parameters (e.g., bias voltage, etching, current, precursor gas, time, and substrate temperature). Working condition of DLC-coated parts also affects the tribological characteristics, such as temperature, sliding speed and load, relative humidity, counter surface, and lubrication media (DLC additive interaction). Different types of lubricated oils and additives are used in engine parts to minimize friction and wear. DLC can be coated to the respective engine parts; however, DLC does not behave accordingly after coating because of lubricant oil and additive interaction with DLC. Some additive interacts positively and some behave negatively because of the tribochemical reactions between DLC coating and additives. Numerous conflicting views have been presented by several researchers regarding this coating additive interaction, resulting in unclear determination of true mechanism of such interaction. However, lubricant additive has been established to be more inert to DLC coating compared with uncoated metal surface because the additive is fabricated in such a way that it can react with metal surfaces. In this article, the tribological characteristics of different types of DLC coating in dry and lubricated conditions will be presented, and their behavior will be discussed in relation to working condition and processing parameters.